Validation of syntaxon names and lectotypifications for some Italian vegetation types - Viciani, Daniele (Mediterranean Botany, 2023)
Based on the results of previous phytosociological works, one concerning the Tuscan Quercus petraea forests, another one concerning Apennine communities belonging to Mulgedio-Aconitetea, and the changes provided in the 4th edition of the International Code of Phytosociological Nomenclature, four association names are here validated and the lectotype of Senecionion samniti alliance here designated.